The Influence of Green Marketing Strategy on Purchasing Decisions with Brand Image as Mediating Variable - Utami, Della Fauzi; Puspitasari , Intan; Ishak , I. (Manunggal Halim Jaya, 2026)
Public awareness of sustainability issues drives changes in consumer behavior, including in choosing environmentally friendly skincare products. This study aims to analyze the influence of green marketing strategies on purchasing decisions and the mediating role of brand image on Emina Natura Pal Series consumers in Purworejo Regency. This study used a quantitative approach with a survey method on 133 respondents selected through purposive sampling. The research instrument was tested for validity and reliability before conducting hierarchical regression analysis. The results showed that green marketing significantly influenced brand image and purchasing decisions. Brand image was also proven to significantly influence purchasing decisions and partially mediate the relationship between green marketing and purchasing decisions. These findings emphasize the importance of building positive brand perceptions through green marketing strategies to encourage sustainable consumer behavior. The practical implication of this study is the importance of beauty industry players integrating sustainability values into their brand strategies. However, this study has limitations regarding regional coverage and the demographic characteristics of respondents. Future research is recommended to use a mixed approach and broader regional coverage.